The restauranteurship of Hong Kong's premium Japanese restaurant market. Issue 1 (18th October 2018) - Baldwin, Watson
Abstract : Purpose: Hong Kong has a global reputation as an entrepreneurial hub. The Japanese restaurant community has grown and evolved over the last three decades into what many consider as a natural secondary market for Japanese food. As such, several Japanese restaurateurs have come to Hong Kong to enter Hong Kong's premium Japanese restaurant market. The purpose of this paper is to explore this market of Japanese restaurateurship in Hong Kong. Design/methodology/approach: One of the closest methodologies within the topic and discipline from Baldwin (2017) focuses on Japaneseness as a measurement of culinary authenticity examining Hong Kong's Michelin rated restaurants. Here, the qualitative approach using semi-structured interviews with the chefs of two sets of premium Japanese restaurants from Japan that expanded in Hong Kong, Sushi Iwa and Sushi Yoshitake. As this paper focuses on the premium and high-end market of Japanese chefs and restaurateurs in Hong Kong, the researcher combined the approaches of Kawahara & Speece and Baldwin to pursue a qualitative methodology using semi-structured interviews. Findings: For this research, the interview process had to be divided into two stages. The first was to speak with long standing members of Hong Kong's Japanese restaurant community. The common thread amongst the restaurateurs was that they were either the sole proprietor or a partner who was financially vested within the company not a form of sweat equity. To respect the privacy of the interviews, questions about exact monetary amounts, number of shares and equity or anything regarding holdings were not asked. The idea was to only examine their responses within the criteria of the research objectives. Research limitations/implications: As the Michelin and premium market of Japanese cuisine is so small, this research can only represent a certain part of the market. Future research could examine other Japanese restaurateurs outside of this market that could be examined to gain a wider perspective of the entrepreneurial strategies they used to start-up their business in Hong Kong. Originality/value: As research in this area is very limited, this paper helps bring restaurateurship in Hong Kong into the academic front. Restaurants are one of the most common entry points for new entrepreneurs in hospitality. This paper may help shed some light on how foreign investment entrepreneurship has been achieved in Asia.